Comparison of conventional and cascode drive of SiC BJTs. Issue 17 (15th April 2019) - McNeill, Neville; Broadmeadow, Mark A. H.; Roscoe, Nina; Finney, Stephen
Abstract : This study compares simple conventional and cascode driver circuits for the SiC bipolar junction transistor (BJT). A low‐voltage silicon metal‐oxide‐semiconductor field‐effect transistor is used in the emitter of the BJT to realise the cascode variant. The circuits are experimentally evaluated when switching a current of 2.5 A and a voltage of 600 V in a buck converter.